Development of Functional Cookie from Kenaf (Hibiscus Cannabinus L.) Seed Meal - Ngah, Choy Mun; Nevara, Gita Addelia; Karim, Roselina (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Kenaf seed (Hibiscus cannabinus L.) is one of the potential and excellent food ingredients of kenaf processing by-products. This study aims to develop functional cookies by incorporating 0% (control), 15%, 20%, 25%, and 30% of kenaf seed meal flour (KSMF). The physicochemical quality of kenaf seed meal cookies (KSMC) revealed that KSMC had higher ash, protein and fat content but lower moisture and carbohydrate content than the control. In terms of texture and colour, the hardness and colour values of the KSMC increased and decreased with increasing levels of KSMF, respectively. Sensory scores on acceptability using hedonic test depicted that KSMF addition had no effect on the overall acceptability score of all the cookies. The finding of this study suggested that 30% of KSMF is suitable for use in the development of functional cookies with improved nutritional quality while maintaining the sensory acceptability of the cookies.